Diminishing deadweight loss through energy subsidy cost recovery - Niall Farrell; Harry Humes (The Economic and Social Research Institute (ESRI), 2022)
Energy subsidies are common. Costs are commonly recovered via an often arbitrarily set uniform consumer levy or electricity price surcharge. We show that an electricity price surcharge is optimal for an Irish case study, despite obvious price distortions. The outcome holds across both first and second-best subsidy applications. When financing first-best energy subsidies (e.g. innovation grants), lost consumer surplus is outweighed by distributional benefits. Energy subsidies are often used as second-best policy to mitigate emissions. We show that an electricity price surcharge is most efficient should there be uninternalised emissions, as the social cost of avoided emissions exceeds the deadweight loss of the policy. This is also less regressive than a uniform consumer levy. We demonstrate these general findings through an Irish case study and quantify the expected magnitude of resulting effects. An electricity price surcharge increases lost consumer surplus by up to 3.3%. Distributional implications are also quantified for Ireland using 2015/16 data; households in the first quintile pay exteuro8.65 less per annum, on average, while households in the fifth quintile pay exteuro 7.07 more per annum, on average. These impacts will grow with the total subsidy burden.
Keywords: 330